Bubble versus other continuous positive airway pressure forms: a systematic review and meta-analysis. Issue 5 (22nd January 2020) - Bharadwaj, Shruti K; Alonazi, Abdullah; Banfield, Laura; Dutta, Sourabh; Mukerji, Amit
Abstract : Background: Use of bubble continuous positive airway pressure (CPAP) has generated considerable interest in neonatal care, but its comparative effectiveness compared with other forms of CPAP, especially in developed countries, remains unclear. Objective: To systematically review and meta-analyse short-term clinical outcomes among preterm infants treated with bubble CPAP vs all other forms of CPAP. Methods: Prospective experimental studies published from 1995 onward until October 2018 comparing bubble versus other CPAP forms in preterm neonates <37 weeks' gestational age were included after a systematic review of multiple databases using pre-specified search criteria. Results: A total of 978 articles were identified, of which 19 articles were included in meta-analyses. Of these, 5 had a high risk of bias, 8 had unclear risk and 6 had low risk. The risk of the primary outcome (CPAP failure within 7 days) was lower with bubble CPAP (0.75; 95% CI 0.57 to 0.98; 12 studies, 1194 subjects, I 2 =21%). Among secondary outcomes, only nasal injury was higher with use of bubble CPAP (risk ratio (RR) 2.04, 95% CI 1.33 to 3.14; 9 studies, 983 subjects; I 2 =42%) whereas no differences in mortality (RR 0.82, 95% CI 0.47 to 1.92; 9 studies, 1212 subjects, I 2 =20%) or bronchopulmonary dysplasia (BPD) (RR 0.8, 95% CI 0.53 to 1.21; 8 studies, 816 subjects, I 2 =0%) were noted. Conclusion: Bubble CPAP may lead to lower incidence of CPAP failure compared with other CPAP forms. However, it does not appear to translate to improvement in mortality or BPD and potential for nasal injury warrants close monitoring during clinical application. Trial registration number: CRD42019120411.